Competitiveness, technology and skills - Lall, Sanjaya; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2001)
This book draws together recent contributions by Sanjaya Lall--leading authority on international investment, technology and industrial policy--on competitiveness and its major determinants. It draws upon his wide experience of competitiveness analysis in Asian and African countries and his recent work on technology and skills. It contains his most important published material as well as previously unpublished articles, and will be of interest to students, researchers and policy analysts interested in industrial development, technology and human resources.
1. What 'competitiveness' is and why it is important -- 2. 'Market-stimulating' technology policies in developing countries : a framework with examples from East Asia (with Morris Teubal) -- 3. Import liberalization and industrial performance : the conceptual underpinnings (with Wolfram Latsch) -- 4. The technological structure and performance of developing country manufactured exports, 1985-98 -- 5. Skills and competitiveness in developing countries -- 6. Multinational corporations, technology development and export competitiveness -- 7. Technological change and industrialization in the Asian newly industrializing economies : achievements and challenges -- 8. India's manufactured exports : comparative structure and prospects -- 9. Competitiveness challenges in the new Asian Tigers : Malaysia, Thailand and the Philippines -- 10. Technology policies in Indonesia -- 11. Transfer and development of technology : Kenya and Tanzania.
Includes bibliographical references and index.
Keywords: Industrial policy -- Developing countries; Technology and state -- Developing countries; Skilled labor -- Developing countries; Competition -- Developing countries; Competition, International; Electronic books